Low-Loss Buried-Heterostructure Optical Waveguide Based on Impurity-Free-Vacancy-Diffusion Quantum Well Intermixing - Yang-Jeng Chen; Rih-You Chen; Chih-Hsien Chen; Yu-Hung Lin; Cong-Long Chen; Po-Yun Wang; Yen-Hsiang Chang; Yi-Jen Chiu (IEEE Photonics Journal)
A new method for fabricating a high-quality buried-heterostructure optical waveguide using quantum well intermixing (QWI) has been demonstrated. By patterning a SiO2 thin film on top of a multiple quantum well (MQW) heterostructure, rapid thermal annealing (RTA) could induce laterally local QWI, resulting in a bandgap blueshift and a simultaneous decrease in the refractive index. Both lateral bandgap and index engineering could be attained along the MQW plane, which could be used for a buried-heterostructure optical waveguide. Two SiO2 strips with 3, 5 and 7 μm windows were fabricated for waveguide on a 1540 nm InGaAsP MQW sample. A 120 nm blueshift under the SiO2 area was observed, leading to the index contrast of 0.07. Far-field optical diffraction measurements were also performed to yield angles of 13.9°, 12.8° and 10.6°. A narrower window resulted in a narrower optical waveguide width and exhibited a larger diffraction angle, suggesting that QWI defined the buried optical waveguide. In addition, an electroabsorption modulator was also made by buried waveguide. A −10 dB low optical insertion loss and a 15 dB high extinction ratio in a 500 μm long waveguide were obtained, indicating that a buried heterostructure could be used for photonic devices and integration applications.